Religious Education and the Crisis of Moral Formation in Ghanaian Schools: Negotiating Ethics, Pluralism, and Social Responsibility - Adam Konadu; Charles Kofi Twene; Dennis Tawiah; Francis Xavier Kabir Mwinkom; Collins Boafo (Social Sciences and Humanities Reviews, 2026)
Background: Religious education remains an integral component of Ghana’s educational system through Religious and Moral Education (RME), which is intended to promote ethical values, discipline, tolerance, and responsible citizenship among students. However, increasing concerns regarding indiscipline, dishonesty, intolerance, and moral decline among students have raised critical questions about the actual effectiveness of religious education in shaping moral behaviour within contemporary Ghanaian schools. Aims: This study aims to examine the influence of religious education on moral development in Ghanaian schools by exploring how moral values are taught, interpreted, and practiced within diverse educational contexts. Methods: The study employed a qualitative multiple-case study design involving selected public and faith-based schools in Ghana. Data were collected through semi-structured interviews, focus group discussions, classroom observations, and document analysis involving teachers, students, school administrators, and religious leaders. The data were analyzed using thematic analysis through coding, categorization, and theme development procedures. Results: The findings indicate that religious education contributes significantly to the promotion of honesty, respect, discipline, responsibility, tolerance, and peaceful coexistence among students. Interactive teaching approaches such as discussions, storytelling, and reflective dialogue were found to strengthen students’ moral reasoning and ethical awareness. Nevertheless, challenges including doctrinal bias, exam-oriented teaching, inadequate teacher preparation, and limited critical engagement reduce the effectiveness of moral instruction in some schools. Conclusion: Religious education continues to play an important role in moral formation and social cohesion in Ghanaian schools. However, its effectiveness depends on inclusive pedagogy, critical reflection, balanced curriculum implementation, and sensitivity toward religious diversity within contemporary educational environments.